Analysis of Learning Styles in Differentiated Indonesian Language Learning Based on Multiple Intelligences in Elementary School Students - Widi Maryani; Retno Winarni; Sukarno (Universitas Negeri Malang, 2025)
Abstract: Recognizing individual diversity is essential for supporting children's learning, particularly in language skills. A differentiated learning approach that aligns with children's learning styles can significantly enhance the effectiveness of language acquisition by addressing specific needs and characteristics. The research method utilized a qualitative approach with a case study design. The subjects were five fifth-grade students during the 2024/2025 academic year. Data collection techniques included document analysis, observation, and interviews. Data was analyzed using the linear approach data analysis technique (John W. Creswell model). The primary objectives of this qualitative case study were to: 1) determine children's language learning style profiles, 2) identify effective ways to teach language skills based on these styles, and 3) measure the impact of differentiated learning, tailored to learning styles, on improving language proficiency. The study identified distinct student characteristics: visual learners relied on sight and preferred neatness; auditory learners depended on hearing and preferred listening; kinesthetic learners were physically active and enjoyed direct practice; interpersonal learners thrived in group settings; and intrapersonal learners preferred independent study. The results affirm that teachers can effectively apply differentiated learning to facilitating the language learning process for all students. Abstrak: Mengenali keragaman individu sangat penting untuk mendukung pembelajaran anak-anak, terutama dalam keterampilan bahasa. Pendekatan pembelajaran berdiferensiasi yang sesuai dengan gaya belajar anak-anak dapat secara signifikan meningkatkan efektivitas penguasaan bahasa dengan mengatasi kebutuhan dan karakteristik spesifik mereka. Metode penelitian ini menggunakan pendekatan kualitatif dengan desain studi kasus. Subjek penelitian adalah lima siswa kelas lima pada tahun ajaran 2024/2025. Teknik pengumpulan data meliputi analisis dokumen, observasi, dan wawancara. Data dianalisis menggunakan teknik analisis data pendekatan linier (model John W. Creswell). Tujuan utama studi kasus kualitatif ini adalah: 1) menentukan profil gaya belajar bahasa anak-anak, 2) mengidentifikasi cara efektif untuk mengajarkan keterampilan bahasa berdasarkan gaya belajar tersebut, dan 3) mengukur dampak pembelajaran berdiferensiasi terhadap peningkatan kemahiran bahasa. Studi ini mengidentifikasi karakteristik siswa yang berbeda-beda: siswa yang belajar secara visual mengandalkan penglihatan dan lebih menyukai kerapian; siswa yang belajar secara auditori bergantung pada pendengaran dan lebih menyukai mendengarkan; siswa yang belajar secara kinestetik aktif secara fisik dan menikmati praktik langsung; siswa yang belajar secara interpersonal berkembang baik dalam lingkungan kelompok; dan siswa yang belajar secara intrapersonal lebih menyukai belajar secara mandiri. Hasil penelitian ini menegaskan bahwa guru dapat menerapkan pembelajaran berdiferensiasi secara efektif untuk mengakomodasi gaya belajar yang beragam ini untuk memfasilitasi proses pembelajaran bahasa bagi semua siswa.